Loss of p32 triggers energy deficiency and impairs goblet cell differentiation in ulcerative colitis - Sünderhauf, Annika; Hicken, Maren; Schlichting, Heidi; Skibbe, Kerstin; Ragab, Mohab; Raschdorf, Annika; Hirose, Misa; Schäffler, Holger; Bokemeyer, Arne; Bettenworth, Dominik; Savitt, Anne G; Perner, Sven; et al. (bioRxiv, 2020)
Abstract Cell differentiation in the colonic crypt is driven by a metabolic switch from glycolysis to mitochondrial oxidation. Mitochondrial and goblet cell (GC) dysfunction have been attributed to the pathology of ulcerative colitis (UC). We hypothesized that p32/gC1qR/HABP1, which critically maintains oxidative phosphorylation, is involved in GC differentiation and hence in the pathogenesis of UC. In UC patients in remission, colonic GC differentiation was significantly decreased compared to controls in a p32-dependent manner. Plasma/serum lactate and colonic pAMPK level were increased, pointing at high glycolytic activity and energy deficiency. Consistently, p32 silencing in mucus-secreting HT29-MTX cells abolished butyrate-induced differentiation and induced a shift towards glycolysis. In mitochondrial respiratory chain complex V-deficient mice, colonic p32 expression correlated with loss of differentiated GCs, resulting in a thinner mucus layer. Conversely, feeding mice an isocaloric glucose-free, high-protein diet increased mucosal energy supply that promoted colonic p32 level, GC differentiation and mucus production. We here describe a new molecular mechanism linking mucosal energy deficiency in UC to impaired p32-dependent GC differentiation that may be therapeutically prevented by nutritional intervention.